Implementasi Penerapan Pemberian Ganti Kerugian Korban Kecelakaan Pesawat: Studi Kasus Lion Air JT-610 PK-LPQ - Pramuditya Syaiful Maarif; Burhanudin Burhanudin (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The purpose of this study is to ascertain the carrier's legal obligation for compensating victims of aviation accidents and the appropriate use of release and discharge documents in compensating victims of the Lion Air JT-610 PK-LPQ plane crash. This study employs an empirical normative research methodology in conjunction with a legislative and conceptual approach. Legislative approach to Aviation Law No. 1 of 2009 and Minister of Transportation Regulation No. PM 77 of 2011 on Air Transport Carriers' Responsibilities. A conceptual approach to issue analysis presupposes the existence of empty standards. The findings of this study indicate that Lion Air has paid compensation in accordance with Law No. 1 of 2009 in the amount of Rp. 1.300.000.000,00 per passenger or victim of the Lion Air JT-610 plane crash, but has violated Law No. 1 of 2009 by utilizing release and discharge documents related to Lion Air's compensation, which contain an exoneration clause or waiver of liability clause, thereby absolving the carrier of responsibility in the event of a plane crash.